The role of job demand, work environment and social support of psychological stress among medical assistants in Mental Institution - Niu Soon, Yen (2024)
Healthcare workers, especially those working in the mental institutions, experience significant levels of stress, which can have a negative impact on their mental and physical health. They often encounter problems such as high job demands, trauma exposure, and stigma, which can lead to poor mental health, including symptoms of post-traumatic stress disorder. Therefore, this study is conducted with the intention to capture factors that might influence psychological stress among medical assistants in mental institution. The study tested three independent variables namely, job demand, work environment, and social support against psychological stress. A total of 140 questionnaire were distributed online using Google form with response rate of 100%. In this study, hypotheses for direct relationhsip were tested using multiple regression analyses. Results showed that only job demand was positively related to psychological stress. The findings indicate that psychological stress tend to increase when they are facing with high workload and given shorter time to complete given task. Though, both work environment and social support were found significant in this study, it was in the opposite direction indicating that both of these factors tend to increase the psychological stress experience by the medical assistants. These findings provide new insight where on issues of psychological stress among medical assistants in mental institution in Malaysia on issues of psychological stress. The question of why having positive work environment and providing social support do not reduce the psychological stress experienced by the medical assistants in mental institution provide opportunity for future research to reconcile these explanations